Comparison of two Different Doses of Intrathecal Tramadol to Prevent Post-Operative Shivering in Patients Undergoing Surgeries under Spinal Anesthesia - Atique ur Rehman Orakzai; Syed Lareb ali shah; Dr. Maqsood Ahmed Siddiqu; beenish Naseem; beenish Naseem; Amina khatoon; Dr. Shahid Hussain (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective: To compare two different doses of Tramadol for prevention of post-operative shivering in patients undergoing surgeries under spinal anesthesia Study Design: Comparative cross-sectional study Setting and Duration of Study: Combined Military Hospital Skardu September 2024 to February 2025 Patients and Methods: All the patients undergoing surgical procedures at operation theater of CMH Skardu under spinal anesthesia were recruited in this study. Patients were divided into two groups for the sake of comparison. Group I had 10mg Tramadol along with routine pre-anaesthetic medication while group II had 20 mg of same medication. Both the groups were observed for 5 hours after the surgery for post-operative shivering or other immediate adverse events in the recovery room. ConclusionResults: Out of 220 patients randomized into two groups for the sake of comparison, 128 (58.2%) took 10 mg Tramadol and 92 (41.8%) took 20 mg Tramadol before induction of spinal anesthesia. Mean age of patients put who were recruited in this study was 34.84 ±10.64 years. When both the groups were compared, post spinal anesthesia shivering and post-operative need for opiate analgesia were found statistically significantly less in group of patients who took 20mg Tramadol than those who took 10mg Tramadol (p-value<0.001). Conclusion: Shivering after the surgery under spinal anesthesia was not uncommon in our study participants. It was concluded that 20mg dose of Tramadol was more effective in preventing post spinal anesthesia shivering as compared to 10mg dose of Tramadol used for same purpose.